Outcome of Down syndrome associated acute lymphoblastic leukaemia treated on a contemporary protocol - Patrick, K; Wade, R; Goulden, N; Rowntree, C; Hough, R; Moorman, A; Mitchell, C; Vora, A (Blackwell Publishing Ltd, 2014)
We report the outcome for children and young people with Down syndrome-associated acute lymphoblastic leukaemia (DS-ALL) treated on a contemporary protocol. Compared with non-DS ALL, patients with DS-ALL had an inferior event-free survival (65·6% vs. 87·7% at 5 years; P < 0·00005) and overall survival (70·0% vs. 92·2%; P < 0·00005). Excess treatment-related mortality - was primarily responsible for the worse outcomes for DS-ALL (21·6% at 5 years, vs. 3·3%, P < 0·00005). Minimal residual disease (MRD) risk status was highly discriminant for relapse in DS patients with 0/28 relapses in the MRD low risk group. © 2014 John Wiley and Sons Ltd.